2010
DOI: 10.3189/172756411795932092
|View full text |Cite
|
Sign up to set email alerts
|

Carbon fluxes through bacterial communities on glacier surfaces

Abstract: There is very little information about the activity of microbial communities on the surface of glaciers, though there is an increasing body of evidence to show that they strongly influence the biogeochemistry of these habitats. We measured bacterial abundance and production in cryoconite holes on Arctic, Antarctic and Alpine glaciers in order to estimate the role of heterotrophic bacteria within the carbon budget of glacial ecosystems. Our results demonstrate an active bacterial community on the surface of gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
107
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 55 publications
11
107
1
Order By: Relevance
“…4 from a modern contribution (e.g., bacteria) rather than abiotic racemization in the river basin. The presence of bacteria and their modification of organic matter (OM) in both subglacial (Sharp et al, 1999) and supraglacial (Anesio et al, 2010) regions have been confirmed in previous studies. As for the Bayelva River basin, previous hydrochemical data (e.g., NO − 3 /Cl − ) also indicated that there is a nitrification process in the soils that contributes to riverine nutrients (Hodson et al, 2002), and hence the presence of bacteria.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…4 from a modern contribution (e.g., bacteria) rather than abiotic racemization in the river basin. The presence of bacteria and their modification of organic matter (OM) in both subglacial (Sharp et al, 1999) and supraglacial (Anesio et al, 2010) regions have been confirmed in previous studies. As for the Bayelva River basin, previous hydrochemical data (e.g., NO − 3 /Cl − ) also indicated that there is a nitrification process in the soils that contributes to riverine nutrients (Hodson et al, 2002), and hence the presence of bacteria.…”
Section: Resultssupporting
confidence: 61%
“…This decoupling of age and stability in glacial DOM is probably due to the contribution of subglacial microbial communities (Sharp et al, 1999). The main sources of organic carbon in glacial meltwa-ter include bed rock and paleosoil at the bottom of glaciers and subglacial microbial activity (Sharp et al, 1999), the proglacial/ice margin (e.g., soils) , and the cryoconite and supraglacial microbial contribution (Anesio et al, 2010;Irvine-Fynn et al, 2012). Unlike temperate glaciers (e.g., alpine glaciers), suspended sediment in high Arctic glaciers becomes increasingly available to the fluvial system through the melt season and hence the particulate organic carbon (POC) output may remain at an elevated level throughout the melt season.…”
Section: Introductionmentioning
confidence: 99%
“…Hamilton et al (2013) reported that viable microorganisms thrive under ice. In addition, several studies showed that cryoconite holes and supraglacial debris are hot-spots of microbial diversity on top of glaciers (Anesio et al, 2009(Anesio et al, , 2010Edwards et al, 2013b;Franzetti et al, 2013) and may thus constitute part of the microbial pioneer communities in recently deglaciated barren soils.…”
Section: Introductionmentioning
confidence: 99%
“…There is a wealth of data on the principal carbon cycling processes (primary production, secondary production, respiration) from the supraglacial ecosystems of the GrIS and other glaciers and ice sheets (e.g., Bagshaw et al, 2007Bagshaw et al, , 2016Foreman et al, 2007;Hodson et al, 2007Hodson et al, , 2010Stibal et al, 2008Stibal et al, , 2012bAnesio et al, 2009Anesio et al, , 2010Telling et al, 2010;Cook et al, 2012Cook et al, , 2016bBellas et al, 2013;Chandler et al, 2015;Rassner et al, 2016;Smith et al, 2016). However, data on rates of microbial exudation (biotic release of dissolved organic carbon (DOC) from living cells), decomposition of particulate organic carbon (POC), and cell mortality on glacier surfaces are currently lacking.…”
Section: The Supraglacial Ecosystemmentioning
confidence: 99%
“…Due to the nature of the supraglacial environment, these are likely to be mostly aerobic chemoheterotrophs, i.e., oxidizing OC compounds by atmospheric oxygen to gain energy while also using OC as a carbon source. Typical rates of secondary production in supraglacial environments are between 10 −7 and 10 −4 g C m −2 d −1 Anesio et al, 2010;Bellas et al, 2013). Monod kinetics may also be appropriate for formulating G H , since heterotrophic growth on GrIS is likely dependent on the concentration of DOC and limiting nutrients .…”
Section: Modeling the Supraglacial Ecosystemmentioning
confidence: 99%